2014
DOI: 10.1111/hdi.12173
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation, high ferritin, and erythropoietin resistance in indigenous maintenance hemodialysis patients from the Top End of Northern Australia

Abstract: Use of erythropoiesis-stimulating agents (ESAs) has improved the management of anemia in patients on maintenance hemodialysis (MHD). Iron deficiency and inflammation cause ESAs resistance and are both common among indigenous people of Northern Australia. As part of quality assurance in our Renal Anaemia Management program, we observed that there was use of higher doses of ESAs and adjuvant iron therapy in our MHD patients. This study aimed to explore the relationship among iron studies, inflammation, ESA respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(26 citation statements)
references
References 41 publications
1
25
0
Order By: Relevance
“…In contrast, HD patients with normal levels of serum hepcidin-25 and ferritin failed to respond to OIT in our study, suggesting that iron absorption and efflux may be inhibited, thereby reducing iron availability for erythropoiesis in HD patients with normal levels of serum hepcidin-25 and ferritin [ 31 ]. This finding has been supported by the following observations: (1) high levels of serum hepcidin-25 and ferritin have been associated with nonresponsiveness to OIT in non-HD patients [ 21 ]; (2) HD patients with high levels of serum ferritin have been resistant to iron supplementation and thus required high dose of iron [ 37 , 38 ]; and (3) HD patients with normal MCV have failed to respond to intravenous iron supplementation [ 32 ].…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…In contrast, HD patients with normal levels of serum hepcidin-25 and ferritin failed to respond to OIT in our study, suggesting that iron absorption and efflux may be inhibited, thereby reducing iron availability for erythropoiesis in HD patients with normal levels of serum hepcidin-25 and ferritin [ 31 ]. This finding has been supported by the following observations: (1) high levels of serum hepcidin-25 and ferritin have been associated with nonresponsiveness to OIT in non-HD patients [ 21 ]; (2) HD patients with high levels of serum ferritin have been resistant to iron supplementation and thus required high dose of iron [ 37 , 38 ]; and (3) HD patients with normal MCV have failed to respond to intravenous iron supplementation [ 32 ].…”
Section: Discussionmentioning
confidence: 91%
“…In support of our finding, previous studies have shown the predictive value of low serum hepcidin-25 for the good response to intravenous iron supplementation in CKD patients not on dialysis [ 22 ]. In addition, HD patients with high levels of serum ferritin [ 37 , 38 ] and non-HD patients with high levels of serum hepcidin-25 [ 21 ] have been resistant to intravenous or oral iron supplementation. In contrast, other reports showed that serum hepcidin-25 was of minimal value in predicting response to intravenous iron supplementation in HD patients [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 2 ] Despite the widespread use of ESA, near 50% ESRD patients do not reach the target hemoglobin (Hb) levels. [ 3 ] Iron deficiency[ 4 ] and imflammation[ 5 ] are the most common reasons for hyporesponsiveness to ESA therapy in ESRD patients. Serum iron, transferrin saturation (TSAT), the ratio of serum iron to total iron-binding capacity (TIBC), multiplied by 100, and serum ferritin levels are commonly used to evaluate iron status.…”
Section: Introductionmentioning
confidence: 99%
“…We looked at ferritin levels over 3 distinct ranges. The thresholds of 1124 pmol/L and 2472 pmol/L are clinically relevant due to association with ESA resistance [36,37] and may be used in the future to identify patients who may benefit from AA supplementation. Regression analysis revealed that in patients with a pre-HD P[AA] ≤ 100 μM, ferritin levels ≥ 1124 pmol/L or ≥2472 pmol/L were not associated with pre-HD P[Ox] reaching 30 μM.…”
Section: Discussionmentioning
confidence: 99%